Influence of O-methylated metabolite penetrating the blood–brain barrier to estimation of dopamine synthesis capacity in human L-[β-(11)C]DOPA PET - Matsubara, Keisuke (Nature Publishing Group, 2014)
O-methyl metabolite (L-[β-(11)C]OMD) of (11)C-labeled L-3,4-dihydroxyphenylalanine (L-[β-(11)C]DOPA) can penetrate into brain tissue through the blood–brain barrier, and can complicate the estimation of dopamine synthesis capacity by positron emission tomography (PET) study with L-[β-(11)C]DOPA. We evaluated the impact of L-[β-(11)C]OMD on the estimation of the dopamine synthesis capacity in a human L-[β-(11)C]DOPA PET study. The metabolite correction with mathematical modeling of L-[β-(11)C]OMD kinetics in a reference region without decarboxylation and further metabolism, proposed by a previous [(18)F]FDOPA PET study, were implemented to estimate radioactivity of tissue L-[β-(11)C]OMD in 10 normal volunteers. The component of L-[β-(11)C]OMD in tissue time-activity curves (TACs) in 10 regions were subtracted by the estimated radioactivity of L-[β-(11)C]OMD. To evaluate the influence of omitting blood sampling and metabolite correction, relative dopamine synthesis rate (k(ref)) was estimated by Gjedde–Patlak analysis with reference tissue input function, as well as the net dopamine synthesis rate (K(i)) by Gjedde–Patlak analysis with the arterial input function and TAC without and with metabolite correction. Overestimation of K(i) was observed without metabolite correction. However, the k(ref) and K(i) with metabolite correction were significantly correlated. These data suggest that the influence of L-[β-(11)C]OMD is minimal for the estimation of k(ref) as dopamine synthesis capacity.